2020
DOI: 10.1038/s41598-020-57530-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Genes Regulating Cohesion Induces Chromosome Instability that May Promote Cancer and Impact Patient Outcomes

Abstract: chromosome instability (cin), or continual changes in chromosome complements, is an enabling feature of cancer; however, the molecular determinants of cin remain largely unknown. emerging data now suggest that aberrant sister chromatid cohesion may induce cin and contribute to cancer. to explore this possibility, we employed clinical and fundamental approaches to systematically assess the impact reduced cohesion gene expression has on cin and cancer. ten genes encoding critical functions in cohesion were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…An XY boundary exclusion filter (<7 µm) was employed to remove partial nuclei along the image periphery, while inclusion filters were employed for area (250-2800 µm 2 ) and mean Hoechst intensity (4500-5 × 10 4 au) to eliminate small nuclear debris (i.e., apoptotic bodies) and mitotic cells, respectively. MN were assessed as detailed previously [55][56][57]. Briefly, MN were operationally defined as small (<1/3 the size of the nucleus), extra-nuclear Hoechst-stained bodies exhibiting no visible attachments with the primary nucleus.…”
Section: Scquantimmentioning
confidence: 99%
“…An XY boundary exclusion filter (<7 µm) was employed to remove partial nuclei along the image periphery, while inclusion filters were employed for area (250-2800 µm 2 ) and mean Hoechst intensity (4500-5 × 10 4 au) to eliminate small nuclear debris (i.e., apoptotic bodies) and mitotic cells, respectively. MN were assessed as detailed previously [55][56][57]. Briefly, MN were operationally defined as small (<1/3 the size of the nucleus), extra-nuclear Hoechst-stained bodies exhibiting no visible attachments with the primary nucleus.…”
Section: Scquantimmentioning
confidence: 99%
“…Single cell approaches have also been developed to quantify and compare surrogate markers of CIN (e.g., CIN-associated phenotypes), including micronucleus formation [28,29] and changes in nuclear areas [29] or human artificial chromosomes [30]. Conceptually, micronuclei are extra nuclear bodies that are found outside the primary nucleus and are hallmarks of CIN that typically arise due to chromosome missegregation events [31][32][33], while changes in nuclear areas and human artificial chromosomes are associated with small and large (i.e., ploidy) scale changes in DNA content, respectively [30,[34][35][36][37][38]. These approaches typically involve quantitative imaging microscopy or flow cytometry that are each capable of rapidly assessing CIN-associated phenotypes in hundreds-to-thousands of cells [28,29,39].…”
Section: Fundamental Concepts In Assessing Cin: Benefits and Limitationsmentioning
confidence: 99%
“…In any case, endpoint approaches offer unparalleled insight into the level of cell-to-cell heterogeneity and population diversity associated with CIN. For example, these endpoint approaches and subsequent cytogenetic validation have been instrumental in expanding our understanding of the molecular determinants of CIN, which includes genes regulating chromosome cohesion and condensation [35,36,[40][41][42], histone modifications [43][44][45][46], microtubule motor proteins [34,47], and ubiquitin regulating complexes [37,48,49]. Only once these single cell approaches are more readily applied in both experimental and clinical contexts will we begin to expand our current understanding of the intimate and causal relationships existing between CIN and cancer so that we can ultimately realize its clinical potential in enhancing case management and predicting clinical outcomes.…”
Section: Fundamental Concepts In Assessing Cin: Benefits and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronuclei are typically defined as having a diameter ≤ 1/3 the size/area of the primary nucleus [1] and their appearance (i.e., micronucleus formation) is frequently employed as an indicator of an underlying genotoxic stress [2,3]. In the past, many genotoxic studies have sought to determine the impact compounds have on genome stability by manually assessing the presence of micronuclei following a treatment [4,5], while more recent studies have employed micronucleus formation assays to uncover genes with pathogenic implications in cancer [6][7][8]. In this regard, numerous cytological studies have identified micronuclei within various cancer contexts including head and neck, ovarian, and breast cancers [9][10][11].…”
Section: Introductionmentioning
confidence: 99%